MORPHOLOGICAL CRITERIA FOR PREDICTION OF SEVERITY OF CROHN’S DISEASE CLINICAL COURSE IN CHILDREN - E. N. Fedulova; E. A. Zhukova; O. A. Tutina; T. A. Kuznetsova; O. V. Shumilova; O. V. Fedorova (Вопросы современной педиатрии)
Aim: to establish prognostic morphological criteria of complicated clinical course of Crohn’s disease in children. Patients and methods: morphometric and histological characteristics of the mucous membrane of the large intestine were studied in 27 patients with colitis form of Crohn’s disease on their first admission to a hospital. Results: the most informative predictive morphological criteria for unfavorable prognosis were the following: predominance of the non-active macrophages tending to aggregation in the lamina propria mucosae; destructive vasculitis; increase in the number of fibroblastic cells with the prevalence of the young forms. Non-active macrophages and immature fibroblasts under hypoxia conditions, associated with necrotizing vasculitits, are the factors which contribute to development of fibrosis in the mucous membrane of the large intestine. Conclusitons: unfavorable prognostic morphological criteria of Crohn’s disease were determined. These criteria allow using more aggressive treatment management («top-down» scheme) with early administration of steroid, cytostatic and anti-cytokine drugs in order to prevent the development of complications due to intestinal fibrosis.